Analysis of Regional Budget Realization against PSAP No. 02 in the Effectiveness of the Financial Report of the Surakarta City DPRD Secretariat (Analysis from an Islamic Worldview) - Divandra Putri Etaprisastia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to assess the effectiveness of budget management and reporting at the Surakarta City DPRD Secretariat for the 2023–2024 period. This study focuses on the application of government accounting standards in recording financial reports, the conformity between the planned budget and its realization, and the identification of the types and causes of budget deviations that arise. In addition, the study also examines the extent to which the budget is used effectively in supporting the implementation of institutional tasks and functions. The method used is a descriptive qualitative approach with data collection through triangulation techniques, which include in-depth interviews, non-participatory observation, and documentation studies of the Budget Realization Report (LRA) and Notes to the Financial Statements (CaLK). Data were obtained from key informants who have direct responsibility in the process of preparing and evaluating financial reports.